Kemampuan literasi matematika siswa SMP pada materi SPLDV melalui problem based learning berbantuan nearpod - Dinda Audina Rahmah; Rahma Siska Utari; Septy Sari Yukans; Dea Alvionita Azka (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2026)
The 2022 PISA results show that the mathematical literacy performance of Indonesian students remains low. This study aims to describe the mathematical literacy abilities of ninth-grade students through the implementation of Problem Based Learning (PBL) supported by Nearpod in the topic of Systems of Linear Equations in Two Variables (SPLDV). The research subjects consisted of 29 students from MTs Negeri 1 Ogan Ilir. Data were collected through written tests in the form of open-ended questions, as well as interviews. The PBL learning supported by Nearpod was carried out in one meeting prior to the administration of the test. The data were analyzed using triangulation to obtain a comprehensive description of students’ mathematical literacy abilities. The findings indicate that the implementation of PBL supported by Nearpod can enhance students’ mathematical literacy, particularly in the aspect of formulating problems. However, students still encounter difficulties in mathematizing contextual information into mathematical models and performing basic calculations accurately. These findings contribute to efforts to improve the quality of mathematics learning through the integration of problem-based learning and interactive technological tools.